Prevalence of birth before arrival and associated factors among postpartum women in southern Ethiopia: a community-based cross-sectional study - Amanuel, Tsedeke; Desalegn, Mitiku; Lukas, Kaleegziabher; Yohannes, Tadele (Frontiers in Medicine, 2024)
Background: Birth before arrival (BBA) constitutes a high-risk newborn population with high perinatal morbidity and mortality. In Ethiopia, most studies and health surveys consider only home and hospital deliveries but do not consider deliveries that take place between the house and health facility. The aim of this study was to assess the prevalence of BBA and its associated factors among postpartum women in Lemo woreda, Hadiya Zone, SNNPR, Ethiopia, 2023.A community-based cross-sectional study was conducted among postpartum women in Lemo woreda, Hadiya Zone, SNNPR, Ethiopia, from April 5 to May 20, 2023.Three hundred eighty-two postpartum women who gave birth six months prior to this study were included. Twelve out of 36 kebeles were selected randomly, and simple random sampling was employed for the selection of participant women. An interviewer-administered questionnaire was used for data collection. A binary logistic regression analysis was computed, and variables with a p value of < 0.25 were included in the final multivariable logistic regression analysis. Model fitness was checked via the Hosmer-Lemeshow goodness-of-fit test (x 2 = 16.04, p value = 0.250). Statistical significance was declared via odds ratios and 95% confidence intervals at a p value < 0.05.The prevalence of BBA among women who gave birth in the last six months preceding this study in the study area was 15.2% (95% CI: 11.8%, 19.1%). In the multivariable analysis, the variables associated with birth before arrival in the final model were having no antenatal care (AOR = 2.63; 95% CI: 1.23, 5.63), having a female autonomy status (AOR = 3.32; 95% CI: 1.12, 9.89), not being knowledgeable about labor symptoms (AOR = 2.15; 95% CI: 1.11, 4.18), and having birth preparedness toward the index birth (AOR = 0.13; 95% CI: 0.05, 0.35).The prevalence of BBA in the study area was unacceptably high. A statistically significant association was observed between birth before arrival and having no antenatal care, dependent women's autonomy status, being not knowledgeable about labor symptoms, and having birth preparedness toward the index birth.